Use of Mobile and Computer Devices to Support Recovery in People With Serious Mental Illness: Survey Study - Noel, Valerie A (JMIR Ment Health, 2019)
BACKGROUND: Mental health recovery refers to an individual’s experience of gaining a sense of personal control, striving towards one’s life goals, and meeting one’s needs. Although people with serious mental illness own and use electronic devices for general purposes, knowledge of their current use and interest in future use for supporting mental health recovery remains limited. OBJECTIVE: This study aimed to identify smartphone, tablet, and computer apps that mental health service recipients use and want to use to support their recovery. METHODS: In this pilot study, we surveyed a convenience sample of 63 mental health service recipients with serious mental illness. The survey assessed current use and interest in mobile and computer devices to support recovery. RESULTS: Listening to music (60%), accessing the internet (59%), calling (59%), and texting (54%) people were the top functions currently used by participants on their device to support their recovery. Participants expressed interest in learning how to use apps for anxiety/stress management (45%), mood management (45%), monitoring mental health symptoms (43%), cognitive behavioral therapy (40%), sleep (38%), and dialectical behavior therapy (38%) to support their recovery. CONCLUSIONS: Mental health service recipients currently use general functions such as listening to music and calling friends to support recovery. Nevertheless, they reported interest in trying more specific illness-management apps.